Solvothermal synthesis of Al2Se3/rGO nanocomposites with excellent electrochemical performance in supercapacitor. (15th August 2023) - Safdar, Muhammad; Awais, Muhammad; Muneer, Sana; Gouadria, Soumaya; Jabeen, Nimra; Iftikhar, Mehak; Waqas, Muhammad; Aslam, Sidra; Javaria,; Asghar, M.; Mirza, Misbah; Tahir, M.B.
Abstract: As a supercapacitor material, transition metal selenide (TMS) can be synthesised in a cost-effective and simple manner. However, it suffers from low-rate capacities and poor cyclic stability due to their easy aggregation and structural instability during charge and discharge cycles. Herein, we report the synthesis of aluminum selenide (Al2 Se3 ) nanorods over reduced graphene oxide (rGO) nanosheets as a novel material using the solvothermal method. The successful formation of Al2 Se3 /rGO nanocomposite was confirmed via XRD (X-ray diffraction), SEM (scanning electron microscopy), and XPS (X-ray photoelectric spectroscopy) and was also investigated for its optical characteristics and electrochemical performance. The optimised Al2 Se3 /rGO sample with 5 wt% and 10 wt% rGO exhibited high specific capacitances of 701.83 Fg −1 and 1138.1 Fg −1, respectively. Moreover, Al2 Se3 /10%rGO nanocomposite as a positive electrode achieves energy densities of 39.57 Wh/kg and power densities of 0.006 kW/kg at current densities 2.5 A/g along with stability up to 2000 cycles, suggesting it to be a significant technological candidate in the future. This work highlights an effective and feasible approach to engineer or construct TMS/rGO nanocomposites for charge storage applications. Highlights: Novel nanomaterial composite of Al2 Se3 /rGO High specific capacitance of 10 % rGO in composite Energy density of 39.57 Wh/kg and power density of 0.006 kW/kg Capacitance retention of 92.5 %